2008
DOI: 10.1111/j.1464-410x.2008.07733.x
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian Uro‐Oncology Group multicentre phase II study of docetaxel administered every 3 weeks with prednisone in men with metastatic hormone‐refractory prostate cancer progressing after mitoxantrone/prednisone

Abstract: PATIENTS AND METHODSThirty patients from four centres were enrolled in the study; all had had previous MP for symptomatic, metastatic HRPC and all had castrate levels of testosterone maintained during therapy. RESULTSAt enrolment, the median age was 69 years, the mean PSA level was 324 ng/dL, and 86% of patients reported pain. There was a PSA response in 57% of the men and a reduction in pain in > 60%; the overall QoL was maintained. There were four cases of febrile neutropenia and two treatment-related deaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…In our study, the PSA response rate ≥50% reduction of the base line level was 42.9%. As Shimazui et al 8 , had recorded an overall PSA response rate of 68.8%, our results were highly comparable with Naito et al 21 , Tannock et al 6 (44.4% and 45%, respectively), on the other hands, Saad et al 23 and Ansari J et al 24 , had recorded a higher response rates ( 57% and 54%, respectively ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, the PSA response rate ≥50% reduction of the base line level was 42.9%. As Shimazui et al 8 , had recorded an overall PSA response rate of 68.8%, our results were highly comparable with Naito et al 21 , Tannock et al 6 (44.4% and 45%, respectively), on the other hands, Saad et al 23 and Ansari J et al 24 , had recorded a higher response rates ( 57% and 54%, respectively ).…”
Section: Discussionsupporting
confidence: 89%
“…respectively. While, Shimazui et al 8 had reported a median time to disease progression of 8.5 months and median overall survival of 12.5 months, Saad et al 23 had reported a median progression-free and overall survival of 5 and 15 months, respectively and Ansari J et al 24 median treatment-free interval of 24 and median overall survival was 13 months. However, Howard et al 25 , had reported in a Canadian retrospective study that among 161 patients with HRMPC docetaxel and prednisone did not perform as well in terms of median survival, as it was shown to in prior clinical trials (17.22 vs. 18.9 months).…”
Section: Discussionmentioning
confidence: 99%
“…Further, these median OS are not only greater than that of nine months after treatment with 55 mg/m 2 DTX [12] or that of 18 months after treatment with 60 mg/m 2 DTX in SWOG 9916 but also consistent with the 15-27 months median OS obtained after treatment with 70-75 mg/m 2 DTX [1,4-6,13,14]. The median OS of 24 months or more achieved in this study was considered to be due to the initiation of DTX therapy with low PSA value as compared with that obtained in the previous reports [1,4-6,13,14], because multivariate analysis performed in this study and the report by Bamias et al [15] demonstrated that OS prolonged when PSA was low at the initiation of DTX therapy. Since the adverse events observed in this study were well tolerated, treatment with 60 mg/m 2 DTX seems to be effective and safe even in EMP-refractory CRPC patients.…”
Section: Discussionsupporting
confidence: 68%
“…For treatment of castration resistant prostate cancer (CRPC) a systemic chemotherapy has been developed in the last years [ 1 3 ]. The chemotherapeutic drug docetaxel (Taxotere®) is given to patients after androgen deprivation therapy (ADT) failure on the basis of improved overall survival, pain reduction, prostate-specific antigen response, and quality of life [ 3 ].…”
Section: Introductionmentioning
confidence: 99%